Multilateral solutions to the erosion of non-reciprocal preferences in NAMA - Patrick Low; Roberta Piermartini; Jurgen Richtering (World Trade Organization (WTO), 2005)
This paper analyzes the risks of preference erosion arising from MFN trade liberalization in manufactured products. It focuses on developing countries that receive non-reciprocal preferences in the markets of United States, EU, Japan, Canada and Australia. The paper estimates preference margins as the difference between non-reciprocal preferential rates received by individual countries and the best available (MFN or better-than-MFN) treatment received on average by all other suppliers. Most previous work on this subject has compared the preferential rates for individual countries with MFN rates alone, which the paper found to have the effect of over-stating the margin at risk from erosion following MFN reductions. The paper also considers the effect of less than full utilization of preference margins by beneficiaries, but a lack of data prevented the inclusion of this additional moderating factor relating to erosion risk.The paper finds that developing countries as a whole do not loose from preference erosion following MFN liberalization, although significant gains and losses underlie the estimate of the average. Almost all least-developed countries either lose from preference erosion or are unaffected by it because their exports are already largely MFN duty-free. A large number of LDCs are in the latter group. The main sectors where preference erosion occurs are textiles, fish and fish products, leather and leather products, electrical machinery and wood and wood products. As regards trade solutions to preference erosion, options are somewhat limited. Improved utilization rates may help certain countries but certainly do not offer a generalized solution. Limited scope exists for expanding the coverage of preference schemes within the destination markets considered in the paper. Other destination markets might offer some prospect, but these are limited by the fact that the markets studied dominate the trade flows of the beneficiary countries.
Keywords: 330; Meistbegünstigung; Außenhandelsliberalisierung; Internationaler Dienstleistungsverkehr; Entwicklungsländer; USA; EU-Staaten; Japan; Kanada; Australien